Private Sector Activities on Research and Development - Tristan Macapanpan (Philippine Institute for Development Studies (PIDS), 1999)
This paper seeks to examine the various approaches to designing and evolving a technological strategy as an integral part of business study. Ideas of Porter, Dussauge, Noori and Maidique are synthesized, which, in turn, helps in analyzing how the private sector chooses its innovation. This framework is utilized to predict what innovation activities the Philippine firms will undertake
Keywords: 330; science and technology; research and development sector; business strategy; technological strategy